Development of a lab-scale hybrid vehicle system for small gasoline engine - Zainul Abidin, Zainul Ameerul Ikhsan (2021)
In a theoretical engine, during the combustion process, oxygen from the intake air would convert all the hydrogen and carbon contents in the fuel into water and carbon dioxide to prove it is in complete combustion. However, this situation never happens in the actual combustion then the usage electricity can solve the global warming issues contributed by the emissions produced from the IC engine by reducing the dependence of the operating system on fossil fuels. Electric vehicles, via electric motors (EM), give a high efficiency compared with internal combustion engines but at a lower average top speed. Combining these two types of systems will produce a hybrid electric vehicle (HEV) system that is able to produce higher efficiency and a moderate average top speed, as well as consuming less fuel. Thus, a hybrid vehicle system will reduce the emissions released, hence reducing the greenhouse effect. The development of a hybrid electric vehicle system, especially for a small gasoline engine. The process involved in the development of a small hybrid system is similar to other larger hybrid vehicle systems. However, the system is more compact in size and has no external gearing system or gearbox system. When developing this type of hybrid system, the drivetrain structure and the Implementing a hybrid system in the vehicle system today will contribute to the environment by decreasing the emissions released into the air. The small gasoline engine in this research refers to a single-cylinder internal combustion engine with capacity below 150 cc. The developed lab-scale hybrid system showed common properties that provided it with some advantages relative to conventional IC motorcycles. Lab-scale setup is design to mimic real-world development system and control perspective. This setup expected to improve overall process control education process because of the hands on experience on modelling, system identification, control design and implementation on an equipment which is closed to real world application. In this study, the performance of the electric motor was under rated. The hybrid system only can be tested in the small range of between 1500 rpm up to 3000 rpm. By using a higher-powered electric motor, better performance and emission characteristics can be obtained, hence showing a bigger picture of the performance of the hybrid system.